2010
DOI: 10.25100/cm.v41i3.707
|View full text |Cite
|
Sign up to set email alerts
|

Chronological versus dental age in subjects from 5 to 19 years: a comparative study with forensic implications

Abstract: Objectives: This study evaluated six methods used in estimating the age of patients attending the Dental School at Universidad del Valle, evaluating dental development by using panoramic radiographs. Additionally, the study determined the sexual identity of the person and the bilateral symmetry of development, the maturity and the chronological eruption of permanent teeth.Materials and methods: This is a descriptive, quantitative and transversal study that evaluated which of the six methods (Logan & Kronfeld; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Recently, there has been an increasing need for fast and inexpensive methods for age determination ( 18 ). Chronological age assessment methods with the help of dental maturation follow-up have been performed by many researchers ( 13 , 14 , 19 , 20 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been an increasing need for fast and inexpensive methods for age determination ( 18 ). Chronological age assessment methods with the help of dental maturation follow-up have been performed by many researchers ( 13 , 14 , 19 , 20 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous authors have shown that Demirjian's approach is the gold standard for determining a person's age based on their teeth, hence this is the technique that was used in the study. [9], [10], [11], [12], [13], [14] Participants in this crosssectional study were assigned at random to one of many age groups. The approach, most likely, has the benefit of rapidly amassing data on enhancement throughout a wide range of ages.…”
Section: Discussionmentioning
confidence: 99%
“…Vol:. ( 1234567890 [52][53][54] . Some papers report an underestimation of chronological age by this method 52,54 , others a slight overestimation 53 .…”
Section: Discussionmentioning
confidence: 99%
“…( 1234567890 [52][53][54] . Some papers report an underestimation of chronological age by this method 52,54 , others a slight overestimation 53 . The absolute mean difference between dental and chronological age is approximately one year 52,54 .…”
Section: Discussionmentioning
confidence: 99%